Clinical pharmacological studies of amoxycillin: effect of probenecid. Issue 3 (June 1979) - Barbhaiya, R; Thin, R N; Turner, P; Wadsworth, J
Abstract : In a study of eight, healthy adult volunteers given 3 g amoxycillin with or without 1g probenecid, significantly higher peak plasma levels of amoxycilin were recorded in the presence (34.96 microgram/ml) of probenecid than in its absence (22.72 microgram/ml). When plasma levels were plotted against time the mean area under the curve was significantly greater for subjects given probenecid than for those given amoxycillin alone. These findings suggest that 3g amoxycillin plus 1g probenecid provide better bioavailability than 3g amoxycillin alone. The plasma levels obtained were several times higher than the minimun inhibitory concentrations (MICs) of most strains of gonococci. Plasma levels in excess of the MICs for most strains were maintained for eight hours with both regimens, but the higher levels in the presence of probenecid support the better clinical results previously reported with this regimen.